Fast patterning of poly(methyl methacrylate) by a novel soft molding approach and its application to the fabrication of silver structures - Mondin, Giovanni; Schumm, Benjamin; Fritsch, Julia; Hensel, Rene; Grothe, Julia; Kaskel, Stefan (Materials Chemistry and Physics, 2013)
A novel single-step approach for the fabrication of poly(methyl methacrylate) structures by soft molding of a 5 wt% solution in acetone is reported. The use of a low weight solution and of a solvent with high volatility ensures a very fast patterning, down to 10 s. In addition, the process is extremely simple and cost-effective, since just one elastomeric mold is needed, and areas as large as 1 cm2 were patterned uniformly and defect-free. The process was applied to the fabrication of silver structures by silver deposition via electroless plating or evaporation followed by poly(methyl methacrylate) removal. Structures of various shapes and sizes, with dimensions in the micrometer and submicrometer range were successfully fabricated, showing the versatility of the process. This silver patterning process is particularly well suited for applications in microelectronics and optoelectronics, such as the fabrication of transparent electrodes for solar cells and displays, manufacturing of metal etching masks and wiring of printed circuits. © 2012 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Evaporation; Lithography; Microstructure; Polymers